What works to recruit general practices to trials? A rapid review [version 1; peer review: 2 approved, 1 not approved] - Fiona Riordan; Daire Buckley; Sheena M. McHugh (HRB Open Research, 2023)
Background: Recruitment challenges are a barrier to the conduct of trials in general practice, yet little is known about which recruitment strategies work best to recruit practices for randomised controlled trials (RCTs). We aimed to describe the types of strategies used to recruit general practices for trials and synthesize any available evidence of effectiveness. Methods: We conducted a rapid evidence review in line with guidance from Tricco et al. Eligible studies reported or evaluated any strategy to improve practice recruitment to participate in clinical or implementation RCTs. PubMed, Embase, and Cochrane Central Library were searched from inception to June 22nd, 2021. Reference lists of included studies were screened. Data were synthesized narratively. Results: Over 9,162 articles were identified, and 19 studies included. Most (n=13, 66.7%) used a single recruitment strategy. The most common strategies were: in-person practice meetings/visits by the research team (n=12, 63.2%); phone calls (n=10, 52.6%); financial incentives (n=9, 47.4%); personalised emails (n=7, 36.8%) or letters (n=6, 52.6%) (as opposed to email ‘blasts’ or generic letters); targeting practices that participated in previous studies or with which the team had existing links (n=6, 31.6%) or targeting of practices within an existing practice or research network (n=6, 31.6%).  Three studies reporting recruitment rates >80%, used strategies such as invitation letters with a follow-up phone call to non-responders, presentations by the principal investigator and study coordinator, or in-person meetings with practices with an existing affiliation with the University or research team.  Conclusions: Few studies directly compared recruitment approaches making it difficult to draw conclusions about their comparative effectiveness. However, the role of more personalised letter/email, in-person, or phone contact, and capitalising on existing relationships appears important. Further work is needed to standardise how recruitment methods are reported and to directly compare different recruitment strategies within one study. PROSPERO registration: CRD42021268140 (15/08/2021)